Mechanical properties of spark plasma sintered ceria reinforced 8 mol% yttria-stabilized zirconia electrolyte. Issue 5 (1st September 2012) - Omar, Shobit; Simpson, Amanda; Balani, Kantesh; Gupta, Alka; Mahato, Neelima; Sharma, Samir
Abstract : Doping of ceria into yttria-stabilized zirconia (YSZ) has been reported to have improved the properties in terms of thermal insulation capability, ionic conductivity, and mechanical- and phase-stability of YSZ for applications as potential electrolyte materials workable at intermediate temperature range (500-700°C). In order to select an appropriate amount of ceria to be added, it is important to understand the effects of the added dopants on phase and microstructure, lattice parameters, and mechanical properties. This paper presents synthesis and characterization (of phase, microstructural, and mechanical properties at micron and nanoscale level) of 8 mol. % Y2 O3 -ZrO2 (8YSZ) containing 0, 5, and 10 wt. % CeO2 via spark plasma sintering. Microstructural analysis has elicited increased grain growth with increasing CeO2 content in 8YSZ. Phase analysis has indicated formation of solid solution with dilation of 8 YSZ lattice upon CeO2 addition. In contrast, isolated ceria rich zones have been identified through energy dispersive spectroscopy (attachment in transmission electron microscope) affirming the formation of CeO2 -8YSZ composite. Microhardness (H), and fracture toughness (KIC ) of CeO2 -8YSZ electrolytes were observed to degrade by 31·2% and 24.0%, respectively, for 10 wt.% CeO2 -8YSZ samples in comparison to that of 8YSZ alone. Whereas, the hardness and reduced modulus of CeO2 -8YSZ samples, evaluated using nanoindentation did not reveal any significant difference in the mechanical properties of the developed composites. Difference in the mechanical properties using Vickers indentation is attributed to the presence of porosity, which is negated in the mechanical property evaluation via nanoindentation. Doping of ceria into yttria-stabilized zirconia (YSZ) has been reported to have improved the properties in terms of thermal insulation capability, ionic conductivity, and mechanical- and phase-stability of YSZ for applications as potential electrolyte materials workable at intermediate temperature range (500–700°C). In order to select an appropriate amount of ceria to be added, it is important to understand the effects of the added dopants on phase and microstructure, lattice parameters, and mechanical properties. This paper presents synthesis and characterization (of phase, microstructural, and mechanical properties at micron and nanoscale level) of 8 mol. % Y2 O3 -ZrO2 (8YSZ) containing 0, 5, and 10 wt. % CeO2 via spark plasma sintering. Microstructural analysis has elicited increased grain growth with increasing CeO2 content in 8YSZ. Phase analysis has indicated formation of solid solution with dilation of 8 YSZ lattice upon CeO2 addition. In contrast, isolated ceria rich zones have been identified through energy dispersive spectroscopy (attachment in transmission electron microscope) affirming the formation of CeO2 -8YSZ composite. Microhardness (H), and fracture toughness (KIC ) of CeO2 -8YSZ electrolytes were observed to degrade by 31·2% and 24.0%, respectively, for 10 wt.% CeO2 -8YSZ samples in comparison to that of 8YSZ alone. Whereas, the hardness and reduced modulus of CeO2 -8YSZ samples, evaluated using nanoindentation did not reveal any significant difference in the mechanical properties of the developed composites. Difference in the mechanical properties using Vickers indentation is attributed to the presence of porosity, which is negated in the mechanical property evaluation via nanoindentation.